Rivers State College of Arts & Science, Port Harcourt, Nigeria - Victor, Barinua Y.; Nzor, Nuka P.; Abolo, Aseinimieyeofori P.; Chikwe, Emenike (Richtmann Publishing, 2012)
It is no news that Nigeria is a blessed country with both human and natural resources with a land area of983,213kms and over 120 million people, as expected though with its own fair share of challenges andopportunity yet unaddressed owning to which the services of management practice becomes eminent andbrings to bear the need for this paper on the challenges of managing in the Nigeria work environment.These challenges were viewed in two perspectives, external and internal with individual peculiarities.Handling our work environment demand collective effort, owing to which the skills of managing play agreater role within the said system. It is our believe then, that we create an institution which promote anideal working environment that captures a more collective interest and speak of collective vision with thebig picture in mind of todayâ€™s issue with the focus on tomorrows challenge. A glance at Nigerian workersshows motivational problems which is traceable to the variety of circumstances as notice in the variousenvironments. These challenges can be addressed by both management and government to introduceuseful and lasting measures, practices to stir the sea of management to meet its â€œbig pictureâ€.